Pengaruh Penggunaan Teknologi Ulir Filter dan Geoisolator pada Produksi Garam Rakyat di Kabupaten Indramayu: Impact of the Utilization of Filter Thread Technology and Geoisolators on Salt Production in Indramayu Regency - Mutiara Salsabiela; Joko Prayitno (Jurnal Teknologi Lingkungan, 2022)
The choice of technology in the production of salt is one of the key factors to obtain higher productivity. Salt farmers in Indramayu Regency have been utilizing a combination of filtration thread technology (TUF) and Geoisolator to increase the quantity and quality of their salt production. The aim of this study was to ascertain the impact of TUF and Geoisolator utilization compared to the traditional method on salt production in Indramayu in 2015 using descriptive analysis. The result of this study shows that TUF and Geoisolator technology produces salt which met the national standard (in accordance with SNI; free from impurities and heavy metal contaminants), and higher productivity than traditional technology. The productivity of TUF and Geoisolator was ± 140 tons/ha, while that of the traditional was ± 92.23 tons/ha, or an increase of 151.8%. The selling price of salt per unit of weight increased with better salt quality. The salt price of TUF and Geoisolator was in the range of 450,000–650,000 IDR / ton (Grade I), while the traditional was in the range of 130,000–450,000 IDR / ton (Grade II). Although the investment cost of the TUF and Geoisolator was 82.2% larger than the traditional, and the operating cost also increased by 42%, the revenue from salt sales increased up to 104.7%. Thus, with higher productivity and quality, total income of salt farmers per unit of area was also higher. With higher investment cost, BEP of the TUF and Geoisolator was longer than the traditional (27 and 21 months, respectively). This result indicates that TUF and Geoisolator technology is a good alternative for improving the economy and welfare of salt farmers. Keywords: TUF, Geoisolator, Salt production, Salt farming, Indramayu ABSTRAK Pemilihan teknologi produksi garam merupakan faktor penting dalam meningkatkan produktivitas garam. Petambak garam di Kabupaten Indramayu telah menggunakan kombinasi Teknologi Ulir Filter (TUF) dan Geoisolator untuk meningkatkan hasil produksi secara kualitas maupun kuantitas. Tujuan kajian ini adalah untuk mengetahui besaran pengaruh penggunaan teknologi TUFG terhadap produksi garam pada tahun 2015 dibandingkan dengan teknologi tradisional, berdasarkan analisis deskriptif dari hasil observasi, wawancara/kuesioner, dan pengumpulan data sekunder. Hasil kajian menunjukkan bahwa penggunaan TUFG menghasilkan garam sesuai standar SNI dengan produksi dan mutu yang lebih baik (terbebas dari kandungan impuritas dan cemaran logam berat) daripada teknologi tradisional. Penggunaan TUFG menghasilkan produktivitas ± 140 ton/ha sedangkan teknologi tradisional menghasilkan ± 92,23 ton/ha, atau terjadi peningkatan sebesar 151,8%. Mutu yang lebih baik membuat harga jual produk per satuan berat menjadi lebih tinggi. Harga jual garam TUFG yang termasuk Kualitas Produksi I (KP I) berkisar antara Rp450.000,- – Rp650.000,- per ton, sedangkan harga jual garam teknologi tradisional yang termasuk KP II adalah antara Rp130.000,- – Rp450.000,- per ton. Meskipun biaya investasi dan biaya operasional dari teknologi TUFG lebih besar dibandingkan teknologi tradisional (masing-masing lebih besar 82,2% dan 42%), namun pendapatan dari penjualan garam dengan teknologi ini meningkat 104,7%. Dengan produktivitas dan kualitas garam yang meningkat tersebut, maka total penghasilan petani garam per satuan luas menjadi lebih tinggi. PBP usaha garam TUFG adalah 27 bulan, sedangkan usaha tradisional 21 bulan. Hasil tersebut mengindikasikan bahwa teknologi TUFG menjadi teknologi alternatif bagi petambak garam dalam meningkatkan perekonomian dan kesejahteraan mereka. Kata kunci: TUF, Geoisolator, Produksi garam, Petambak garam, Indramayu